2005
DOI: 10.1111/j.1399-3011.2005.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

‘100 years of peptide synthesis’: ligation methods for peptide and protein synthesis with applications to β‐peptide assemblies*

Abstract: A brief survey of the history of peptide chemistry from Theodore Curtius to Emil Fischer to Bruce Merrifield is first presented. The discovery and development of peptide ligation, i.e. of actual chemical synthesis of proteins are described. In the main chapter, 'Synthesis of Proteins by Chemical Ligation' a detailed discussion of the principles, reactivities and mechanisms involved in the various coupling strategies now applied (ligation, chemical ligation, native chemical ligation) is given. These include cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(108 citation statements)
references
References 125 publications
(157 reference statements)
0
99
0
9
Order By: Relevance
“…Besides this, it was shown that oxime ligation represents a highly efficient method for conjugation of various biomolecules [23][24][25][26]. Particularly, we and others have reported that aminooxy function can be easily incorporated to anomer position of sugars [27][28][29] and that this modification enables the quantitative coupling to peptide containing either aldehyde or ketone moieties [18,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Besides this, it was shown that oxime ligation represents a highly efficient method for conjugation of various biomolecules [23][24][25][26]. Particularly, we and others have reported that aminooxy function can be easily incorporated to anomer position of sugars [27][28][29] and that this modification enables the quantitative coupling to peptide containing either aldehyde or ketone moieties [18,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the methodology is rapidly being changed by evolving strategies that overcome some of the limitations of the process. 96 Several strategies have been tried, and based on their observations it was suggested that a Nlinked 2-mercaptobenzyl group could form the basis of a new peptide ligation chemistry ( Figure 42). The model requires tailoring the mercaptobenzyl skeleton for lability.…”
Section: Scheme 51mentioning
confidence: 99%
“…The centrality of the amide linkage, as found in polypeptides and proteins, in the maintenance of life hardly needs restatement. Numerous strategies, resulting in a vast array of protocols to synthesize biologically active polypeptides and proteins, have been demonstrated (3,4). Central to reiterative polypeptide bond formations was the discovery and remarkable development of solid-phase peptide synthesis (SPPS) (5,6).…”
mentioning
confidence: 99%